Nas entrelinhas da segmentação de palavras: juntar ou separar? - Santos, Joseane Azevedo Oliveira Lins dos (2017)
This study has the purpose presenting the result of a research on unconventional segmentations of words performed with children of the second year of elementary school. Because it is a work developed with children in the process of literacy and thinking about the contribution to a more significant study, we decided to use parlendas, as well as working through children's popular games, it greatly facilitates the study of nonconventional segmentation: hyper segmentation and hypo segmentation because parlendas are attractive texts and have small verses, easy to memorize. We observed that, in the literacy process, students have a lot of difficulty in segmenting words, and therefore end up joining or separating words differently from the ones proposed by the standard, precisely because they transpose the knowledge of orality into writing without any or few teacher's intervention. The separation between the words of a sentence can cause doubts in students who are beginning to have contact with the written language, therefore, are difficulties that once unresolved in the base, in the initial years, can be dragged into the later school years. We understand, based on Kleiman (1996); Soares (2009); Ferreiro (1999; 2011); PCN (1997), that exploits the reading and writing through playful activities, directed to the initial years, helps the students' learning, since it allows the adequate contact with the textual diversity since the first steps in the work with writing. And, in fact, we could verify that of the total of 10 children who participated in our practice, 06 understood the formalization of the segmentation in writing after the sequence of activities applied.